Fabrication of mesoporous crystalline microparticles of poly(ether sulfone) via solvent-induced crystallization. (6th May 2022) - Samitsu, Sadaki
Abstract: Mesoporous polymer microparticles are promising for energy, environmental, and biomedical applications. A linear polymer microparticle is desirable from the perspective of polymer recycling. In this study, mesoporous crystalline microparticles of a commercially available high-performance polymer, poly(ether sulfone) (PES), were prepared. Solvent-induced crystallization of PES in nitrobenzene resulted in nearly spherical microparticles with an average size of 5 μm and narrow size distribution. The microstructure and mesoporosity of the microparticles were characterized with scanning electron microscopy, X-ray diffraction, differential scanning calorimetry, and nitrogen adsorption/desorption, which gave a pore size distribution peaking at 7 nm with a porosity of 0.44. Fourier-transform infrared spectroscopy, Raman spectroscopy, and thermogravimetric analysis confirmed the cocrystal of PES and nitrobenzene. The formation mechanism of the PES microparticles was elucidated based on the theory of polymer spherulite formation. This study gives an insight on solvent-induced crystallization of rigid high- T g polymers useful for the mesoporous polymer particle fabrication. Graphical abstract: Image 1 Highlights: Solvent-induced crystallization of poly(ether sulfone) (PES) was investigated. Nitrobenzene induces crystallization of PES and forms a polymer-solvent cocrystal. The cocrystal spontaneously makes uniform microparticles with 5 μm diameter. The microparticles gives large mesoporosity with specific surface area of 200 m 2 /g. The method is promising as a facile preparation of polymer microparticles.